Factores de riesgo cardiovascular modificables en adolescentes escolarizados de Ibagué 2013 (2017)
ABSTRACT: To describe the modifiable cardiovascular risk factors among adolescent students in the district one of the city of Ibague in the second half of 2013. Methodology: A crosssectional study with 149 students; using 4 modules of global school health survey (gshs), anthropometric measurements and blood pressure, non-parametric tests for the analysis of risk factors as sociodemographic and clinical characteristics; bivariate analysis to determine differences of modifiable cardiovascular risk factors by age, sex and type of educational establishment. Results: The prevalence of sedentary lifestyle was 97%; 59% risk of alcoholism; unhealthy eating 53%; 13% overweight and obesity; current smoker teenager 9%, and finally, hypercholesterolemia 7%. Discussion: the risk factors in adolescents had a high prevalence even without established disease indicate, however the continuity of these behaviors can lead to cardiovascular problems and social level staff. Conclusions: This study provides a critical line based on the implementation of promotion and prevention strategies in adolescents for reducing morbidity and mortality from cardiovascular disease of the Tolima population, should include the creation of opportunities for recreation and sport control of alcohol and snuff and nutrition for mothers and owners of establishments that increase the daily intake and the supply of healthy foods including education.